Prevalence of young-onset diabetes and associated physical activity profile in southern India - Anupama Harihar; G. Arun Maiya; Sahana Shetty; K.N. Shivashankar; N. Shyamasunder Bhat (Clinical Epidemiology and Global Health)
Background/objective: A temporal shift is noticed in the age of diagnosis of type 2 diabetes mellitus among young adults globally. Physical inactivity is a significant contributor to the higher prevalence of young-onset diabetes in India. This study aims to estimate the prevalence of young-onset diabetes in southern India and to identify the physical activity level and barriers in young adults. Methods: This is a cross-sectional study including individuals aged 18–40 years. A total of 273 participants were included by random selection of individuals attending a tertiary hospital for routine checkups. In the first stage, the prevalence of type 2 diabetes was estimated using capillary blood glucose level evaluation. The second stage includes the profiling of physical activity & identification of barriers to physical activity among physically inactive individuals using a self-reported questionnaire. Result: The overall prevalence of young-onset type 2 diabetes was found to be 17.2 %. Pre-existing type 2 diabetes was 11.3 %, while 5.8 % of new cases were found with no previous history of diabetes. In males, the prevalence was 10.6 %, whereas in females, it was 6.5 %. The majority of individuals with young-onset type 2 diabetes were physically inactive, and the most common barriers identified were lack of time, willpower, and energy. Conclusion: This study reveals a high prevalence of type 2 diabetes below the age of 40 years in India. Screening for diabetes by the age of 25 years is highly recommended. Management strategies are needed to overcome the identified barriers and promote physical activity in young adults.